النظام القانوني للإجراءات الإدارية : دراسة مقارنة - د. قيدار عبد القادر صالح; انسام علي عبدالله (PROSPECTIVE RESEARCHES, 2023)
Administrative procedures are considered as one of the guarantees which provides legal protection to insividulas which has not been legalized but derived from general principles of the law imposed by proper legal logic or what administrative judicature determines or applied by the administrative office like daily work concerning each case separately. In this research we depend on a comparative analystic approach in two sections; the first includes the definition of administrative procedure, the second sheds light on the main guarantees of procedures. This study has come up with a set of conclusion among which is the necessity of legalizing administrative procedures in a special lead system like other civil and punitive procedures. In addition state employees should include a clear number (14) of (1991) of statement which the employer has the right to see his file before or after starting any investigation to have full information about the charges related to the employee. The study has also concluded that it is necessary that the new Iraqi constitution for the year 2000 should imply a statement concerning a general frame in which the administrative office can follow neutrally in administrative work.